Boilerplate Clauses, International Commercial Contracts and the Applicable Law - Cordero-Moss, Giuditta (Cambridge : Cambridge University Press, 2011)
With the aim of creating an autonomous regime for the interpretation and application of the contract, boilerplate clauses are often inserted into international commercial contracts without negotiations or regard for their legal effects. The assumption that a sufficiently detailed and clear language will ensure that the legal effects of the contract will only be based on the contract, as opposed to the applicable law, was originally encouraged by English courts, and today most international contracts have these clauses, irrespective of the governing law. This collection of essays demonstrates that this assumption is not fully applicable under systems of civil law, because these systems are based on principles, such as good faith and loyalty, which contradict this approach.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Standardized terms of contract; Foreign trade regulation